2011
DOI: 10.1144/sp356.8
|View full text |Cite
|
Sign up to set email alerts
|

Water ice sublimation-related landforms on Mars

Abstract: Sublimation-related landforms are ubiquitous on Mars, especially at mid to high latitudes. This paper reviews the main landforms interpreted to form due to sublimation of subsurface ice on Mars. Pits, knobs and dissected terrains are classical landforms thought to form due to subsurface ice sublimation as observed with high-resolution imagery. Sublimation-related processes on Mars are strongly latitude dependent, with sublimation being increasingly important from high (.608) to low latitudes (down to 258) due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Hecht, 2002;Hecht and Vasavada, 2006;Levin and Weatherwax, 2004). Mangold (2011) considered it unlikely that any equatorial ice occurs close to the surface today, but commented that its presence at depths exceeding 10 m cannot be excluded. The area of Meridiani explored by Opportunity lies approximately 2 o S of the equator (Fig.…”
Section: Ground Icementioning
confidence: 99%
See 1 more Smart Citation
“…Hecht, 2002;Hecht and Vasavada, 2006;Levin and Weatherwax, 2004). Mangold (2011) considered it unlikely that any equatorial ice occurs close to the surface today, but commented that its presence at depths exceeding 10 m cannot be excluded. The area of Meridiani explored by Opportunity lies approximately 2 o S of the equator (Fig.…”
Section: Ground Icementioning
confidence: 99%
“…They argued that in such a situation water could diffuse into the subsurface, allowing a significant amount of ice to condense in the regolith in a few thousand years. Jakosky et al (2005) suggested that this state could have existed as recently as a few decades ago and low-latitude water-ice may have survived to the present day if isolated from the atmosphere, for example by a cemented layer in the soil or simply by very fine-grained regolith which, it has been argued, could inhibit sublimation and preserve ice, even for billions of years and even at the equator (Smoluchowksi, 1968;Mangold, 2011). In the deep trough of Valles Marineris which lies between the equator and about 10 o S latitude, the persistence of enormous volumes of ancient relict ice, protected from sublimation by a cover of ablation till, has been postulated by Gouronc et al (2014).…”
Section: Ground Icementioning
confidence: 99%
“…This scenario would imply different stages of glaciation in Martian history. Polygonal fractures are caused by thermal contraction of ice‐rich apron materials (Mangold, 2011), but in this case are much more rectangular than other Martian polygons (Figure 7b). As the thermal emission is relatively low, it is likely that the lobate and degraded apron materials still contain some amount of ice, while the smoother materials are nearly ice‐free dusty materials.…”
Section: Resultsmentioning
confidence: 97%
“…Sublimation could play a role in crust formation on Mars, but this is restricted to higher latitudes (>60°) and is unlikely to be a major mechanism for crust formation in equatorial regions (Mangold 2011), where the two remaining ExoMars landing sites are located.…”
Section: Discussionmentioning
confidence: 99%